Unravelling population structure and marker trait association using SSR markers among the identified drought tolerant rice landraces (Oryza sativa L.) - Shanmugam Manju Devi; John Amalraj Joel; Muthurajan Raveendran; Ramamoorthy Pushpam; Sengalan Muthuramu; Raman Pushpa; N. Sritharan; Periyasamy Prasanna; Ramalingam Suresh (Czech Journal of Genetics and Plant Breeding)
With climate change, plants face numerous stresses, notably drought for rice cultivation. Improving rice drought tolerance is vital for sustainable production in water-scarce regions. Identification of drought tolerant genotypes at the seedling stage of the crop contributes to build a climate resilient genotype during the period of water scarcity and under challenging environmental conditions. Hence, polyethylene glycol-6000 (PEG-6000) induced drought conditions could be used for testing the drought tolerance in rice at an earlier stage of the crop. Optimization of PEG-6000 concentration for screening index at -6 bar was done using three drought-tolerant and two drought-susceptible check varieties based on probit analysis. Subsequently, 100 rice landraces underwent PEG-6000 induced drought screening at -6 bar and a total of 32 genotypes were selected as tolerant. After 14 days of treatment, the nine observations viz. germination %, root length (cm), shoot length (cm), number of secondary roots, fresh weight (g), dry weight (g), shoot/root ratio, root/shoot ratio and vigour index were recorded. Variance analysis, revealing significant genetic variation among genotypes for all studied traits, indicating genetic variability. Post hoc analysis confirmed notable variation among treatments. Principal component analysis revealed three components, with the first three accounting for 88.89% of total variability. With respect to the biplot, the ten genotypes viz., IRGC109, IRGC403, IRGC448, IRGC461, IRGC466, IRGC486, IRGC508, IRGC518, IRGC527 and IRGC535 are the seedling stage drought tolerant genotypes based on shoot length, number of secondary roots and vigour index. Population structure classified the accessions into two subpopulations, reflecting diversity. The allele frequency divergence is 0.095 which is a measure of fixation index revealing that the moderate divergence is not extremely pronounced. Genetic diversity, assessed through 26 SSR markers selected from drought tolerant QTLs and markers related to vigour index, exhibited 100% polymorphism with 115 alleles and an average PIC value of 0.61 per primer. Shannon index varied between 0.34 (RM212) and 1.96 (RM252), averaging 1.18. Six SSR markers viz., RM246, RM302, RM252, RM219, RM251, and RM486 were associated with the six key traits viz., shoot length, root length, number of secondary roots, dry weight, shoot/root ratio, and root/shoot ratio respectively offering valuable resources for selecting drought-tolerant accessions as it provides the first step in the selection of genotypes based on the key traits.